Amne Gine Mafatanon (We're Brothers) “The Concept of Brotherhood Amid Religious Differences Between Gamta Village and Magei West Misool District of King Ampat” - Lisnawati, Agustin; Wihel, Muhammad Romli (Proceeding International Conference on Science and Engineering, 2020)
This article aims to understand how the "Amne Gine Mafatanon" treats brotherhood amidst religious differences between Gamta village and Magei village West Misool District of King Ampat Islands. Gamta Village is a Muslim village and Magei Village is a Christian village, but both villages are adjacent to the island surrounded by oceans and forests, and the two villages are separated by a road about 300 meters. In this article there are two focus questions, first how do the people of the village of gamta and magei village understand the relationship between the brothers? Secondly, why do the people of Gamta village and Magei village maintain a brotherly bond between the two? Thirdly, how is the traditional model that embraces the brotherhood values of the village gamta and magei village ?. This article usesmethods field research by obtaining primary and secondary data as supporting data in the writing of this article. The results of this study cover the ways in which the people of Kampung Gamta and Kampung Magei engage in brotherhood amidst religious differences and look at the values inherent in the tradition shared between these two villages as a bond of brotherhood.